Differentiating Identities Within an Extreme Sport: A Case Study of Mountain Biking Print Advertisements - McEwan, Kieren; Weston, Neil; Gorczynski, Paul (Frontiers in Psychology, 2018)
The work of McEwan (2016) has questioned the assumed homogeneity of mountain biking in terms of culture and sporting values, leading to the suggestion that there may be differing patterns of identity within the various formats of the sport. This is also supported by McEwan and Weston’s (2017) findings, which advanced knowledge of the mountain biking industry by defining the differing pluralised segments within the market and highlighting their hierarchical nature in relation to the cost of products. This therefore leads to a question over whether differing markets are reflected in differing identities among varying consumer groups within the sport of mountain biking. Thus, this study sought to establish what these identity characteristics are through an analysis of a sample of mountain biking magazine advertisements (N=568). The analysis was conducted using a sequential Ethnographic Content Analysis (Altheide, 1987) followed by a Quantitative Content Analysis (Berelson, 1952) mirroring the approaches used by Cann (2012) and William, Ylänne and Wadleigh (2010) in their studies of the portrayal of identity within magazine advertisements. Results of this analysis highlighted five identity characteristics (places of play, equipment functionality, risk taking, competitiveness, activity aesthetics), three of which varied significantly between differing formats of mountain biking (risk taking, competitiveness, activity aesthetics). Activity aesthetic was established as a component of risk-taking rather than an independent identity characteristic and therefore risk taking along with competitiveness formed the basis of a refined four-format activity categorisation within mountain biking and the production of a model of participant archetypes.